Rencana Aksi Pengembangan Industri Kreatif Kuliner Berbasis Media Online Di Kota Malang - Yusadi, Rofifah; Waluyo, Budi Sugiarto; Setyono, Deni Agus (Jurnal Tata Kota dan Daerah, 2018)
Creative economy is a new sector in the Indonesian economy. Based on Presidential Instruction (Inpres) Number 6 Year 2009 on Creative Economy Development, the government has supported creative economy policy through creative industry. One of the creative industries sub-sector in Malang is culinary culinary that reach 160.000 users in 2013. However, the existence of online culinary has not been recorded by the government and there has been no study of local product development in RPJMD. Therefore, this research is needed related to the identification of online culinary characteristics and the preparation of action plans of its development. Based on stakeholders analsis, Industrial and Trading Department become the executant of strategic planning. Based on the results of research on 96 units of online culinary, there are 3 factors of value shift which is changes in production, distribution, and marketing processes that can be used as the basis for action plans based on value proposition that is operational excellence. This research comes out into 1 vision, 3 missions with 10 different strategies and 22 action plans for the development of online culinary creative industry in Malang City.Keywords: Creative Industry, Online Culinary, Strategic Palnning, Operational Excellence